The Development of Isolated and Underdeveloped Silalahi II Village to be A Developed Village in The Aspect of Agriculture and Tourism - Utomo, Budi; Sembiring, Marheni; Tandjung, Kasmir (Talenta Publisher Universitas Sumatera Utara, 2018)
Silalahi II Village is located at the end of Silahisabungan Sub-district which borders with Toba Samosir Regency. As the main road access to other villages is blocked because of landslide and erosion in many places, the village becomes isolated and underdeveloped. The only possible access to the village is through water by using boats or canoes. Difficult access to the village increases burden that have to be borne by local people; thus, they cannot rise from prolonged poverty to the present. To develop this village, assistance from higher institutions which collaborate synergistically in one series of PPM activities would be required. Based on the priority of the problem, the implementation team of PPM would focus on opening and improving 11 km road access that was blocked for a long time in the village. The work was performed using excavator and bulldozer. In addition, a training which aimed to increase income of the farmers in the village was also conducted by the PPM team. High quality of red onion seeds which was expected to be one of the village’s mainstay products were introduced to the farmers in the training. The village would also be promoted as an alternative tourism village because of its potential of natural beauty. Finally, this village is expected to be established as an assisted village partnered with University of Sumatera Utara (USU) to be the icon and the major driver of the village’s development, and one of the science-techno and tourism park models.